The effect of cognitive rehabilitation on daily functioning of patients with Alzheimer’s disease: a systematic review and meta-analysis of clinical trials - Ren, Shuyu; Pan, Fangfang; Jin, Jie (Frontiers in Neurology, 2024)
Background: Alzheimer's disease (AD) is the most prevalent type of dementia and represents 60-80% of dementia cases. AD affects over 32 million people globally, and 8.1% of affected females and 5.4% of affected males were older than 65 years. Cognitive rehabilitation focuses on helping patients develop individualized strategies to obtain or maintain optimal functioning. As of now, there is no complete and systematic meta-analysis on the effects of cognitive rehabilitation on cognitive functioning in AD patients. Objectives: To provide the most recent and extensive pooled analysis and evidence and explore the influence of cognitive rehabilitation on overall cognitive functioning in patients with AD. Methods: We searched articles through several databases such as PubMed, Cochrane Library, Embase, and Web of Science, from the inception to June 2023. Studies on cognitive stimulation, cognitive training, and cognitive interventions, and non-English articles were excluded. The outcome measures encompassed the effects of cognitive rehabilitation on the overall cognitive functioning of people with AD (e.g. verbal fluency, behavioral memory, neuropsychiatric status and occupational performance levels). Results: A total of 14 clinical trials were included in this analysis. The meta-analysis showed that cognitive rehabilitation significantly improved quality of life (WMD: 2.87; 95% CI: 0.79, 4.95; p = 0.007) and occupational performance levels (WMD: 1.53; 95% CI: 0.43, 2.63; p = 0.007) in patients with AD. However, it did not show a significant effect on other domains of specific cognitive functions in patients with AD. Conclusion: Cognitive rehabilitation exhibited a moderate to large impact on both quality of life and occupational performance levels in people with AD. Future studies are required to explore the potential of various cognitive interventions across specific domains, so as to provide more insights into the management of AD.